(untitled) (Docentes 2.0 Journal, 2026)
Strengthening socio-emotional skills in secondary school students is a priority challenge within the educational system, due to its direct impact on mental health, academic performance, and school coexistence. The purpose of this study was to conduct a systematic review of research on the development of these competencies, with special attention to the Latin American context, to identify advances, limitations, and potential areas for improvement. The research was framed within the humanistic paradigm, using a systematic method with a qualitative approach, a narrative-thematic design, and a cross-sectional, bibliographic-documentary type of study. Thirteen studies on the socio-emotional development of secondary school adolescents were analyzed, with a focus on the Peruvian and Latin American contexts. The results showed progress in school coexistence, emotional self-regulation, and responsible decision-making. However, difficulties persisted related to teacher training, the availability of pedagogical resources, and the sociocultural conditions that influence the implementation of educational strategies. Overall, the findings led to the conclusion that socio-emotional tutoring programs constitute an effective alternative when implemented in a comprehensive, sustained, and contextually tailored manner, tailored to students’ real needs.